Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5194/isprsarchives-xl-1-w5-115-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multi Band Insar Analysis of Subsidence Development Based on the Long Period Time Series

Abstract: ABSTRACT:The SAR Interferometry (InSAR) application has shown great potential in monitoring of land terrain changes and in detection of land deformations such as subsidence. Longer time analysis can lead to understand longer trends and changes. Using different bands of SAR satellite (C-from ERS 1-2 and Envisat, L-from ALOS) over the study area, we achieve knowledge of movements in long-term and evaluation of its dynamic changes within observed period of time. Results from InSAR processing fit with the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Finally, the displacement time series for each PS point along the LOS were derived by separating the phase components of the interferometric phase. Research has shown that use of the StaMPS and the PSI method in SARPROZ software yields consistent results for the same datasets [31,32], while we found that StaMPS was more computationally intensive. Therefore, we used SARPROZ software to process the high amount of TerraSAR-X datasets.…”
Section: Land Subsidence Monitoring Using the Psi Techniquesupporting
confidence: 53%
“…Finally, the displacement time series for each PS point along the LOS were derived by separating the phase components of the interferometric phase. Research has shown that use of the StaMPS and the PSI method in SARPROZ software yields consistent results for the same datasets [31,32], while we found that StaMPS was more computationally intensive. Therefore, we used SARPROZ software to process the high amount of TerraSAR-X datasets.…”
Section: Land Subsidence Monitoring Using the Psi Techniquesupporting
confidence: 53%
“…In addition, the burst terms of "human activity," such as groundwater extraction, subway development, mining, and urban construction, are also identified as the main factors leading to land subsidence [58,60,61]. Besides, "climate change" also reinforced the role of human activities to have a new direction in the research of land subsidence [62,63].…”
Section: High-frequency Termsmentioning
confidence: 99%